Engineering biomimetic bone marrow niche with gene modified mesenchymal stromal cells for ex vivo culture of human hematopoietic stem and progenitor cells - Sevanthy Suresh; Vigneshwaran Venkatesan; Manoj Kumar K. Azhagiri; Gokulnath Mahalingam; Prathibha Babu Chandraprabha; Mohankumar K. Murugesan; Sanjay Kumar; Saravanabhavan Thangavel; Srujan Marepally (Stem Cell Research & Therapy)
Abstract Background Hematopoietic Stem and Progenitor Cells (HSPCs) gene therapy has shown significant progress, with commercial approval for at least four distinct haematological disorders, and poised for a rapid expansion in the upcoming years. Despite these advancements, the ex vivo culture of HSPCs continues to present significant challenges. The stress induced by ex vivo culture can negatively impact transplantation outcomes, while the need for exogenous cytokine supplementation contributes to the high costs associated with gene therapy products. Methods We developed genetically modified human bone marrow MSCs (GM-MSCs) secreting cytokines such as Stem cell factor (SCF), Thrombopoietin (TPO), FMS-like tyrosine kinase-3-ligand (FLT3L), and Interleukin-3 (IL3), closely resembling bone marrow cellular niche to augment HSPCs culture. Results HSPCs proliferate on GM-MSCs akin to standard conditions, devoid of external cytokine supplementation and these HSPCs retain their stem cell characteristics, colony-forming potential, stemness gene signatures, and capacity for long-term multilineage reconstitution in NBSGW mice. We demonstrate that our biomimetic feeder layer supports and alleviates stress associated with Homology Directed Repair (HDR) mediated gene-editing of HSPCs for fetal haemoglobin reactivation for a potential application in β-hemoglobinopathies gene therapy. Conclusion Our GM-MSCs offer a compelling alternative to traditional cytokine supplementation by establishing a biomimetic bone marrow niche that fosters HSPC expansion while maintaining their stemness. These findings underscore the potential of engineered MSCs to revolutionize ex vivo HSPCs culture, ultimately enhancing their therapeutic value for gene therapy applications.